Strategi Peningkatan Minat Jamaah dalam Mengikuti Kegiatan Keagamaan di Masjid - Mubarok, Zulfa Muntaha Al; Fakhruddin, Agus (Muttaqien Publishing, Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STAI DR. KH. EZ. Muttaqien Purwakarta, 2025)
This research examines strategies for increasing congregational interest in participating in religious studies at the Ash-Siddiq Mosque in Bandung City, with a focus on the problem of how to increase congregational participation in studies with general and salafi-specific themes. The aim of this research is to convey the effectiveness of the communication strategies implemented, such as the use of social media, packaging interesting and relevant study themes, as well as direct interaction through the mosque community, and identifying internal factors such as personal motivation of the congregation and external factors such as social factors that influence interest. congregation. The research methodology used is a qualitative approach with a case study method, through data collection techniques which include direct observation of lecture activities, structured interviews with mosque administrators and congregation, as well as analysis of related documents such as study schedules, activity reports, and congregation participation data. The research results show that relevant study themes, such as discussions of contemporary religious issues, have succeeded in increasing congregational interest. Social support from the mosque community, such as organizing small study groups, as well as using social media for promotion, increases congregation participation, especially from younger age groups. This strategy significantly increased the average number of congregations attending each study compared to the previous period. However, there are challenges such as limited transportation access and busy schedules. This research suggests solutions to overcome obstacles, such as adjusting study schedules more flexibly, and diversifying promotional media to reach a wider audience. These findings can be applied in other mosques by adopting social media-based communication strategies, packaging study themes that suit the needs of the congregation, and strengthening interactions through the mosque community. This approach is not only relevant for increasing congregational participation, but also provides practical guidance for mosque managers in managing religious study programs effectively and sustainably.